2014
DOI: 10.14260/jemds/2014/2410
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Efficacy of Local Steroid Injection and Extracorporeal Shockwave Therapy in the Treatment of Plantar Fascitis

Abstract: Subtrochanteric fractures extending below lesser trochanter are always difficult to treat and their higher incidence of unsatisfactory results are noted after operative treatment. There are various implants available for fixation but in this study we did 95 DEG ANGLED PLATE FIXATION BY MIPO TECHNIQUE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…The most common group is 31-40 years (53%). This is comparable to a study by Rajan Sarad et al [15] (2014) majority of patients (152) falling between age group of 31-50 years. In a study by Jeroen C et al [13] (2015) in 58 patients, the mean age was 48.7 years old (SD ± 10.3).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The most common group is 31-40 years (53%). This is comparable to a study by Rajan Sarad et al [15] (2014) majority of patients (152) falling between age group of 31-50 years. In a study by Jeroen C et al [13] (2015) in 58 patients, the mean age was 48.7 years old (SD ± 10.3).…”
Section: Discussionsupporting
confidence: 90%
“…Side in present study: Right side was most commonly involved 52%, while the bilateral involvement is 13%, Rajan Sarad [15] (2014) showed that Bilateral plantar fasciitis was found in 25% patients. Jeroen C et al [13] (2015) studied a total of 61 feet in 58 patients, the right side was treated in 26 patients (42.6%).…”
Section: Sex Distributionsupporting
confidence: 44%
See 2 more Smart Citations
“…Plantar fasciitis significantly diminishes the quality of life, affecting approximately 10% of the global population over their lifetime. 3 The prevalence of plantar fasciitis varies globally, with rates of 7.5% in the United Kingdom (UK), 3.6% in Australia, 59% among individuals aged 40 to 50 in India, and 57.8% in Saudi Arabia. For approximately 90% of cases, conservative treatments like stretching, nonsteroidal anti-inflammatory drugs, night splints, strapping, orthoses, and adjustments to footwear prove effective.…”
mentioning
confidence: 99%